Perception and Utilisation of Information and Communication Technology (ICT) in the Management of Diabetes in Children: Insights From Health Students in Indonesia - Mustamu, Alva Cherry (Scripta Medica, 2024)
Background/Aim: The management of diabetes in children necessitates active involvement from diverse stakeholders, encompassing parents, lecturers, medical experts, nutritionists and technology-facilitated information and communication technology (ICT). In this context, medical students play a crucial role in the management of diabetes in children. Aim of this study was to delineate the perceptions and utilisation of ICT in the management of diabetes in children among students in Indonesia.Methods: This study employed the cross-sectional method, enlisting participants from bachelor and diploma programs in midwifery, nursing and nutrition at the Health Polytechnic of the Ministry of Health, Indonesia. Data were gathered through the distribution of questionnaires via the WhatsApp platform. The questionnaire encompassed respondent demographics, knowledge about diabetes in children, perceptions and utilisation of ICT in the management of paediatric diabetes, factors influencing ICT perception and utilisation and the efficacy of ICT implementation in paediatric diabetes management. The collected data were subjected to univariate and multivariate analyses, employing structural equation modelling with partial least squares.Results: The analytical findings revealed a noteworthy correlation between perception factors and the effectiveness of managing diabetes in children. Nevertheless, ICT utilisation and knowledge about paediatric diabetes did not exhibit significant individual influences on the effectiveness of diabetes management in children. These findings underscored the significance of a comprehensive understanding of diabetes, a favourable perception towards ICT utilisation and engagement in activities involving ICT to enhance the effectiveness of paediatric diabetes management.Conclusion: The utilisation of ICT in the management of paediatric diabetes by health students holds significant potential for enhancing effectiveness in management. This necessitates a profound understanding of diabetes, a favourable perception regarding ICT utilisation and active engagement in ICT-related activities as integral components of paediatric diabetes management strategies.